Arahan Penanganan Permukiman Kumuh di Desa Balantang Kecamatan Malili Kabupaten Luwu Timur - Yesimiel Pabubung; Agus Salim; Rusneni Ruslan (Journal of Urban Planning Studies, 2022)
The purpose of this study is to identify what factorsonly the cause of the slums and formulate directionhandling of slum settlements in Balantang Village, Malili DistrictEast Luwu Regency.This research approach uses a qualitative approach andquantitatively by collecting quantitative data which is thenwhich then uses Multiple Regression analysis to measurehow much influence then using a descriptive analysis toolQualitative to formulate directions for handling slum settlements.The main conclusion of this study is that there are seven factors thataffect the occurrence of slums in Balantang Village, DistrictMalili, East Luwu Regency, including the condition of buildings, waterwaste, clean water, infrastructure condition, solid waste, fire protectionand land status. While the factors that have no effect aredrainage.